(3CSGSjGJ EOGQI GdeNGWQ (B:s (3age GdEOGQI GdaYGdI ddeNGWQ hJbjjegG hJfajPgG (B/s - (3ghHcf, Hhds; (3HOhj, eGgQ OQjOs; (3ghHcf, Hhd(B.s ((3GdQjGV (B:s (3LGeYI Gdedc SYhO ddfTQ,s, 2022)
(3CSGSjGJ EOGQI GdeNGWQ gh ebOeI TGedI ddeNGWQ GdJLGQjI hJdc GdNGUI HGdCYeGd GdJj JajO cdG ef GdWdHI hGdeJNUUjf aj GdeNGWQ Ydi MO ShGA, EP jhaQ GdcJGH JZWjI TGedI ddCWQ GdCSGSjI dJNWjW GSJeQGQjI GdCYeGd, hEOGQI eNGWQ GdeDSSI, hEOGQI eNGWQ GdeTGQjY(B. (3hJcef CgejI GdcJGH Hchfg GdOdjd GdfgGFj ddJYGed eY CfhGY eNJdaI ef GdeNGWQ GdJj JhGLggG GdeDSSGJ(B. (3ceG jbOe GdcJGH Yf WQjb CeKdI GdMGdI GdOhdjI PGJ GdUdI, HeG aj Pdc TQcGJ EjQcShf (BEricsson(3, h fjJhhQc Qjd (BNetwork Rail(3, h jhfjdjaQ (BUnilever (3, JMdjdG cGedG ddJZjQGJ aj eLGdGJ GdeNGWQ GdeYGUQI, HeG aj Pdc SdSdI GdJhQjO, hGdeNGWQ GdEdcJQhfjI, hKbGaI GdeNGWQ hJbHdgG, hGdJMSjfGJ aj JhKjb EOGQI GdeNGWQ, hGdEHdGZ GdbGfhfj Yf GdeNGWQ(B.s
(3jTJed Ydi edGMb(B.s
Keywords: (3EOGQI GdeNGWQs